2019
DOI: 10.1063/1.5110696
|View full text |Cite
|
Sign up to set email alerts
|

The impact of manganese substitution on the structure and properties of tetrahedrite

Abstract: The crystal structure of the tetrahedrites Cu12-xMnxSb4S13 (x = 0, 1) has been studied by powder neutron diffraction between room temperature and 773 K. At all temperatures investigated, manganese exclusively occupies tetrahedral sites, while the trigonal-planar sites contain only copper. In situ diffraction data confirm the stability of the tetrahedrite phase up to 773 K, with no evidence of copper mobility at elevated temperatures. Analysis of atomic displacement parameters indicate that there are low-energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
(42 reference statements)
1
11
0
Order By: Relevance
“…This phenomenon could also be connected with the liquid-like nature of copper ions, which is more probable in Cu-rich tetrahedrite phases. As is often reported for the superionic argyrodites [24,60], as well as tetrahedrites [48,61,62], the migration of Cu ions can strongly disturb phonon propagation. To verify the TE performance of the investigated samples, the density of the state effective mass m * was calculated using the Kane band model.…”
Section: Samplementioning
confidence: 83%
“…This phenomenon could also be connected with the liquid-like nature of copper ions, which is more probable in Cu-rich tetrahedrite phases. As is often reported for the superionic argyrodites [24,60], as well as tetrahedrites [48,61,62], the migration of Cu ions can strongly disturb phonon propagation. To verify the TE performance of the investigated samples, the density of the state effective mass m * was calculated using the Kane band model.…”
Section: Samplementioning
confidence: 83%
“…The dimensionless figure of merit (ZT) of Cu performed long-term and careful melting processes; raw elements were heated to 923 K, maintained for 12 h, cooled to room temperature, and then annealed at 723 K for two weeks. Guélou et al [18] also conducted long-term and multi-step processes; samples were mechanically alloyed for 6 h, annealed at 973 K for 3 h, and cooled to 823 K for 30 h. The furnace was then cooled to room temperature, and finally, the ingot was crushed and subjected to a second annealing at 823 K for 30 h. In the present study, however, a single tetrahedrite phase exhibiting a high level of ZT was obtained by MA within 24 h without post-annealing.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study [10], undoped Cu 12 Sb 4 S 13 exhibited a ZT of 0.66 at 723 K. In this study, as the Mn content increased, both the thermal conductivity and PF increased. As a result, Cu 11.7 Mn 0.3 Sb 4 S 13 exhibited the highest ZT of 0.75 at 723 K. Wang et al [17] reported a ZT of 0.89 at 700 K for Cu 11.5 Mn 0.5 Sb 4 S 13 prepared by encapsulated melting and HP.Guélou et al[18] obtained a ZT of 0.56 at 573 K for Cu 11 MnSb 4 S 13 produced by MA and HP. Wang et al[17]…”
mentioning
confidence: 99%
“…Considering the valence and coordination of each element, the charge balance of tetrahedrite can be expressed as [6,7]. To improve the dimensionless figure of merit (ZT), partial substitutions at the Cu, Sb, or S sites have been made with doping elements, including transition metals such as Ni, Co, Fe, and Mn at the Cu site [8][9][10][11], Te or As at the Sb site [12,13], and Se at the S site [14].…”
Section: Introductionmentioning
confidence: 99%